Frozen shoulder and other shoulder disturbances in Parkinson's disease. Issue 1 (January 1989) - Riley, D; Lang, A E; Blair, R D; Birnbaum, A; Reid, B
Abstract : The frequency of shoulder disturbances, particularly frozen shoulder, has not been assessed previously in Parkinson's disease. In a survey of 150 patients compared with 60 matched control subjects a significantly higher incidence of both a history of shoulder complaints (43% vs. 23%) and frozen shoulder (12.7% vs. 1.7%) was found in the Parkinson's disease population. Those developing a frozen shoulder had initial disease symptoms indicative of akinesia twice as frequently as tremor while the ratio was reversed in those without frozen shoulder. In at least 8% of the patients frozen shoulder was the first symptom of disease, occurring 0-2 years prior to the onset of more commonly recognised features. Parkinson's disease should be added to the list of causes of frozen shoulder, and clinicians must be aware that the latter is often the presenting symptom of Parkinson's disease.